Assessing the Relation Between Social Support and Depression among Patients Undergoing Hemodialysis in Kerman City - neda asadi; zahra royani (Tehran University of Medical Sciences, 2015)
Background: Depression is a common disorder with incremental trend among patients with hemodialysis. This study conducted in order to determine correlation between social support and depression among patients undergoing hemodialysis of Kerman city. Materials and Methods:  This study was a cross-sectional one. 182 hemodialysis patients referred to health centers of Kerman were selected by census sampling method. data was collected Using questionnaires  including demographic information, Beckchr('39')s Depression Questionnaire (BDI) and Social Support Questionnaire (ESSI: Enriched Social Support Instrument) and analyzed  by SPSS  software version 17 utilizing descriptive statistics (mean and standard deviation) and Pearson Correlation Coefficient test. Results: 68.1% of the subjects had some degree of depression. Also, 83% of participants reported good social support. Furthermore, Assessing the relation between depression and social support revealed an inverse relationship between depression and social support (P =0.005), increasing social support occurred decreasing depression as well.  Conclusion: Study results indicated high prevalence of depression among the patients. It seems special attention in should be paid to psychological issues in hemodialysis wards. Nurses can prevent depression incidence by recognizing high risk individuals in term of perceiving social support among these patients.